The Influence of Profitability, RETA, Liquidity, Leverage, Company Size, and Corporate Governance on Financial Distress - Saputri, Nuraisya Arya; Santoso, Pramana Ridha (Research of Accounting and Governance, 2023)
This study examines how financial distress is affected by profitability, liquidity, Leverage, retained earnings to total assets, firm size, and good corporate governance. This study focused on real estate companies listed on the Indonesia Stock Exchange between 2014-2018. This study relies on secondary data. The sample for this study, which includes 17 firms, was chosen using purposeful sampling. Panel Data Analysis was used with the Eviews application to analyze the data. According to research, leverage and profitability positively and significantly affect financial distress. The liquidity ratio and retained earning to total assets(RETA) to has a positive but insignificant effect on financial distress. Meanwhile, the size of a company and good corporate governance have a negative and insignificant impact on financial distress. At the same time, all variables significantly impact financial distress. Keywords: financial distress, profitability, liquidity, leverage, RETA, size, corporate governance